Can the Inclusion of Calendar and Temperature Effects Improve Nowcasts and Forecasts of Construction Sector Output Based on Business Surveys? - Marcus Scheiblecker (Austrian Institute of Economic Research (WIFO), 2010)
For nowcasting and short-term forecasting of industrial production and GDP, business surveys are a vital source of information. They cover information of the recent past as well as developments in the near future. Whereas variations in industrial production indices potentially cover weather conditions as well as variations due to the different number of work days, it is unclear to which extent business surveys mirror them as well. Ignoring such information can lead to model misspecifications if used for nowcasting or forecasting. This paper sheds light on the effects of temperature changes as well as the varying number of work days on business survey results and on the production index of the Austrian construction industry. We find that survey data do not contain sufficiently the effects of the different number of work days necessary for explaining variations in industrial production of the construction sector. No statistical evidence was found that changing temperatures beyond their typical seasonal pattern influence the survey results and production.
Keywords: 330; Frühindikator; Zeit; Wetter; Prognoseverfahren; Produktivität; Bauwirtschaft; Österreich